Simplify radical expression

Simplify radical expression

Postby Guest » Tue Jan 29, 2019 4:55 am

[tex]\frac{3\sqrt{3}+\sqrt{6}}{\sqrt{6}-\sqrt{2}*2\sqrt{3}+3}[/tex]
Guest
 

Re: Simplify radical expression

Postby nathi123 » Tue Jan 29, 2019 7:36 am

A=[tex]\frac{3\sqrt{3}+\sqrt{6}}{\sqrt{6}-2\sqrt{6}+3}=\frac{\sqrt{3}(3+\sqrt{2)}}{3-\sqrt{6}}=\frac{\sqrt{3}(3+\sqrt{2)}}{\sqrt{3}(\sqrt{3}-\sqrt{2})}[/tex]
because [tex]\sqrt{2}*2\sqrt{3}=2\sqrt{2}.\sqrt{3}=2\sqrt{6} ; 3=(\sqrt{3})^{2}[/tex]
[tex]\Rightarrow A=\frac{3+\sqrt{2}}{\sqrt{3}-\sqrt{2}}.\frac{\sqrt{3}+\sqrt{2}}{\sqrt{3}+\sqrt{2}}=3\sqrt{3}+3\sqrt{2}+\sqrt{6}+2[/tex].

nathi123
 
Posts: 19
Joined: Sun Sep 17, 2017 1:56 pm
Reputation: 17


Return to Exponents and Radicals



Who is online

Users browsing this forum: No registered users and 1 guest